Numerical Simulation and Experimental Study on Flow Field in a Swirl Nozzle - Yicheng Sun; Yufan Fu; Baohui Chen; Jiaxing Lu; Wanquan Deng (Shock and Vibration)
In order to study the internal flow characteristics and external droplet velocity distribution characteristics of the swirl nozzle, the following methods were used: numerical simulations were used to study the internal flow characteristics of a swirl nozzle and phase Doppler particle velocimetry was used to determine the corresponding external droplet velocity distribution under medium and low pressure conditions. The distributions of pressure and water velocity inside the nozzle were obtained. Meanwhile, the velocities of droplets outside the nozzle in different sections were discussed. The results show that the flow rate in the swirl nozzle increases with the increase in inlet pressure, and the local pressure in the region decreases because of the excessive velocity at the internal outlet section of the swirl nozzle, resulting in cavitation. The experimental results show that under an external flow field, the minimum droplet velocity occurs in the axial direction; starting from the axis, the velocity first increases and then decreases along the radial direction. Swirling motion inside the nozzle and velocity variations in the external flow field occur under medium and low pressure conditions. The relationship between the inlet pressure and the distributions of water droplets’ velocities was established, which provides a reference for the research and development of the swirl nozzle.